Synthesis, characterization and evaluation of new piperazinium/dipiperidinium dicationic-based molten salts and ionic liquids as catalysts for some organic reactions / Lia Zaharani - Lia , Zaharani (2021)
The new ionic liquids and molten salts including 4,4’-trimethylene-N,N’-dipiperidinium sulfate [TMDPH2]2+[SO4]2-, 4,4’-trimethylene-N,N’-dipiperidinium chlorosulfonate [TMDPH2]2+2[ClSO3]-, 1H,4H-piperazine-diium dichlorosulfonate [PZH2]2+2[ClSO3]- were designed and synthesized. The chemical structure elucidation of these ionic liquids and molten salts was performed by 1D NMR, FTIR, and mass spectra. Then, the correct structure was elucidated by COSY experiment and Raman spectroscopy. Some physical properties, thermal behavior, and thermal stability of these ionic liquids and molten salts were determined and reported. The formation of a two-protonic acid salt namely 4,4’-trimethylene-N,N’-dipiperidinium sulfate [TMDPH2]2+[SO4]2-, instead of namely 4,4’-trimethylene-N,N’-dipiperidinium hydrogensulfate was evidenced by NMR analyses. The catalytic of this ionic liquid was demonstrated in the esterification reaction of n-butanol and glacial acetic acid under different conditions. The desired acetate was obtained in 62-88% yield without using a Dean-stark apparatus under optimal conditions. α-Tocopherol (α-TCP), a highly efficient form of vitamin E, was also treated with glacial acetic acid in the presence of the ionic liquid, and O-acetyl-α-tocopherol (Ac-TCP) was obtained in 88.4% yield. The formation of 4,4’-trimethylene-N,N’-dipiperidinium chlorosulfonate [TMDPH2]2+2[ClSO3]- and 1H,4H-piperazine-diium dichlorosulfonate [PZH2]2+2[ClSO3]- was indicated that the chlorosulfonic acid could not act as a sulfonating agent in the reaction with secondary amines like 4,4’-Trimethylenedipiperidine (TMDP) and Piperazine (PZ) probably due to more steric hindrance of the sulfur atom by chlorine and oxygen atoms. Then, the dual solvent-catalyst activity of these ionic liquids was demonstrated for the synthesis of novel triazole-pyrimidines through a one-pot three-component reaction under mild conditions. The arene diazonium saccharin derivatives were initially produced from various substituted aromatic amines; subsequently, these intermediates were treated with a greener organic iodide for the preparation of the aryl iodide. The arene diazonium saccharin intermediates could be stored in the liquid phase in a refrigerator for a long time with no significant loss activity. The ionic liquids were retrieved and reused several times without reducing their catalytic efficiency.